A variational simulation framework for the analysis of load distribution and radial displacement of cylindrical roller bearings. (May 2020) - Aschenbrenner, Alexander; Schleich, Benjamin; Tremmel, Stephan; Wartzack, Sandro
Highlights: Elastic half space approach is integrated in statistical variation simulation. Density based sensitivity analysis combined with k-d trees. Geometric deviations cause noticeable variation of cylindrical roller bearings. Controlling the roller diameters decreases the radial displacement variation. Abstract: In many technical systems, rolling bearings are critical machine elements concerning accuracy and lifetime. Their load distribution and radial displacement are directly linked to the accuracy and the fatigue life of rolling bearings. However, load distribution and radial displacement form a complex interdependency. Geometric deviations further influence this mutual connection. Although there are several approaches to determine the load distribution and the radial displacement, most of them are either too simplistic, allowing only the consideration of dimensional deviations, or too sophisticated and therefore unsuitable for a statistical evaluation of geometric deviations. Hence, the main purpose of this contribution is to provide a method for the determination of load distribution and radial displacement of cylindrical roller bearings that allows the consideration of geometric deviations as well as statistical evaluation of these deviations. Moreover, applying the method to a use case shows, whether the consideration of geometric deviations in the determination of load distribution and radial displacement is reasonable. The novelty of the contribution is, therefore, the provision of a statistical variational simulation framework for the analysis of load distribution and radial displacement of rolling bearings.